Pengembangan Aplikasi Pembelajaran Ilmu Tajwid Menggunakan Pemrograman Java Android - Erni Rihyanti; Endah Budiyati (Jurnal Informatika Universitas Pamulang, 2021)
Tajweed is a very important science to learn how to read the Koran, a person will not be able to read the verses of the Koran without knowing the correct and good knowledge of tajwid. However, in this modern era, many have left books as literature. Therefore, the embedding of tajwid into android devices is very helpful for the community in learning. Android is a Linux-based operating system developed by Google. Google provides android studio software as the official IDE for making android applications. Making applications with android studio software using the Java programming language, while the appearance of the application is made using XML. Making applications in scientific research is made in several stages, namely starting with planning, needs analysis, application design, application creation, testing and distribution of applications. After going through all these stages, this scientific research resulted in an application with the name Tajwid Android. This application can only be operated on mobile phones with a minimum of the Jelly Bean version of the Android operating system. The android tajwid application can provide information about the science of recitation with a display that is easy to understand and attractive. This Tajweed Learning Application is published on the internet so that it can be accessed easily by the public.